Higher Education Research: Between Crass Empiricism and Critique - Szadkowski, Krystian (Sensus Historiae, 2023)
This essay develops a reflection on the methodology and theory-making capacity of contemporary higher education research. This relatively marginal area of social reflection has been a source of knowledge feeding powerful processes of transformation of the university sector in recent years. A reflection on the methodological limitations of this area seems essential if one wants to counteract the processes destroying contemporary forms of knowledge development in universities. In the essay, the crass empiricism of higher education research is countered by another strand of reflection—Marxism with its method of critique. By revealing an interest in the ontology (political and historical) of a specific strand of Marxism indebted to the work of György Lukács and Antonio Negri, the essay proposes a starting point for a methodology of critical higher education research.